Dlaczego nie ma taśm z powstania wielkopolskiego? - Marek Hendrykowski (Images)
The article is a monographic study of the moving picture of Wielkopolska Uprising 1918–1919. The author indicates the reasons of a lack of film archives concerning Posnanian War.